Recent climate changes over the Tibetan Plateau and their impacts on energy and water cycle: A review - Yang, Kun; Wu, Hui; Qin, Jun; Lin, Changgui; Tang, Wenjun; Chen, Yingying (Global and planetary change, 2014)
The Tibetan Plateau (TP) exerts strong thermal forcing on the atmosphere over Asian monsoon region and supplies water resources to adjacent river basins. Recently, the Plateau experienced evident climate changes, which have changed atmospheric and hydrological cycles and thus reshaped the local environment. This study reviewed recent research progress in the climate changes and explored their impacts on the Plateau energy and water cycle, based on which a conceptual model to synthesize these changes was proposed and urgent issues to be explored were summarized. The TP has experienced an overall surface air warming and moistening, solar dimming, and wind stilling since the beginning of the 1980s. The surface warming depends on elevation and its horizontal pattern is consistent with the one of the glacier change. Accompanying the warming was air moistening, and both facilitated the trigger of more deep-clouds, which resulted in solar dimming. Surface wind speed declined from the 1970s, as a result of atmospheric circulation adjustment caused by the differential surface warming between the Asian high-latitude and low-latitude. The climate changes had weakened the thermal forcing over the TP. The warming and wind stilling lowered the Bowen ratio and led to less surface sensible heating. Atmospheric radiative cooling was enhanced, mainly by outgoing longwave emission from the warming planetary system and slightly by solar radiation reflection. Both processes contributed to the thermal forcing weakening over the Plateau. The water cycle was also altered by the climate changes. The wind stilling may have weakened water vapor exchange between the Asia monsoon region and the Plateau and thus led to less precipitation in the monsoon-impacted southern and eastern Plateau, but the warming enhanced land evaporation. Their overlap resulted in runoff reduction in the southern and eastern Plateau regions. By contrast, more convective precipitation over the central TP was triggered under the warmer and moister condition and yielded more runoff; meanwhile, the solar dimming weakened lake evaporation. The two together with enhanced glacier melts contributed to the lake expansion in the central TP.